Dialectical approach for structural and functional management in the health-improving and recreational motor activity system of the population - Oleksandr Aghyppo; Galina Putiatina (Kharkiv State Academy of Physical Culture, 2017)
Purpose: substantiate the content of structural and functional management system of recreational motor activity. Material & Methods: analysis of literature sources and documents, system approach, dialectical approach, system-functional analysis, organizational analysis. Results: the dialectic of cognition of structural and functional management system of recreational motor activity presupposes a connection between theory and practice; the principles of cognition of the real world, the determinism of phenomena, the interaction of external and internal, objective and subjective. Conclusion: achievement of the main goal of recreational motor activity system of the population at the state and regional levels is provided by the solution of a complex of tasks.